Religious Education, Social Inclusion and Interreligious Literacy in England and Australia - Byrne, Catherine (Journal for the academic study of religion, 2014)
This article examines the contentious nature of religion in relation to questions of interreligious literacy and education. It connects the concept of cultural tolerance to a particular interpretation of religious literacy' in the education policy environment, and examines religion-related education governance structures. I draw on examples from state-funded Australian government schools, against a backdrop of social inclusion' policy. First, two different, ideologically based, styles of inclusion', and their variant styles of governance, will be de?ned. These two styles can be described as passive' (economically focused and inherently limited) inclusion, and active' (socially focused, and critically, consciously broad) inclusion. The article explores the political basis of these two styles of inclusion and how they encourage or discourage minority voices within democratic processes. The article then analyses how these styles of inclusion affect contributions, from minority voices, to policy development and practice in relation to religion in state schools. Inclusive policies in education in the past few decades have targeted socio-economic (often racial and location-based) and ability differentials. A lack of inclusion policies which specifically address cultural (particularly religious) barriers highlights the limitations of an economically focused social inclusion agenda.